(untitled) (Journal of Educational Sciences, 2023)
The article points out the results of the research of a competent professional education specialist activity aimed at developing creative abilities of trainees. In the modern multilingual education system great importance is attached to teaching a foreign language, increasing students’ interest and motivating language learning. Through the use of active teaching methods that develop creativity, it is possible to activate students and create a harmonious learning environment. The authors analyzed the concepts of competence, creativity and conducted a survey on the use of innovative and creative teaching methods by teachers. The survey involved 100 respondents: school teachers, graduate students, teachers of educational centers. More than 77% of respondents believe that it is necessary to use a creative approach in teaching foreign languages; more than 86.3% of respondents consider it is necessary to use critical thinking methods to increase the effectiveness of teaching foreign languages and develop creativity. It is crucial to prepare a creative environment for teaching foreign languages according to 86% of respondents. Respondents stated out methods as the most useful of specific methods: 73.3% chose “picture gallery”, of which 57.8% chose “quality line” and 53.3% chose the “mind mapping” option. In the final part of the survey, several methods were proposed to obtain information about the extent to which teachers use critical thinking techniques. Key words: educational process, development of creative abilities, creativity, competency, pupils.